The implementation of environmental management accounting and environmental reporting practices: a social issue life cycle perspective - Mokhtar, Norsyahida; Zulkifli, Norhayah; Jusoh, Ruzita (TechMind Research, 2014)
While the pressure of legitimacy was found to greatly influence companies’ environmental reporting (ER) practices, being environmentally responsible however is not necessarily reflected through positive and descriptive environmental information. Unless companies begin to truly commit to upholding environmentally responsible, that is, to be accountable towards their business environmental impacts, the issue of incompleteness and incredibility of ER will remain topical. For companies to effectively measure and report their environmental performance, the implementation of Environmental Management Accounting (EMA) is essential as conventional accounting systems disregard the generation of environmental information. Using social issue life cycle theory as an interpretive lens, this paper aims to propose a theoretical framework to investigate the relationship between the extent of EMA implementation and ER practices.